A comparative analysis of the level of aggression between female and male judokas society - Marta Wojdat; Patrycja Janowska; Małgorzata Pujszo; Robert Stępniak (Kazimierz Wielki University, 2017)
Aim: The comparison the level of aggression of women and men in the judo population, against the background of the average aggression of the Polish society Material and Methods: A group of 77 former and still practicing judokas (30 women and 47 men) were tested using a questionnaire to determine the aggression level of "Aggression Questionnaire" Buss, Perry, Amity Institute in Polish adaptation. Results: Women had lower levels of physical aggression than men. Reduced feelings of hostility among women and men made the judo environment different from the average Polish population. Conclusions: Only the lower level of physical aggression in women is discriminating against the judo environment. The lower level of sense of hostility is a significant distinctive for the entire judo community.